1981
DOI: 10.1111/j.1471-4159.1981.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 3,4‐Dihydroxyphenylalanine and Deuterated 3,4‐Dihydroxyphenylalanine to Alcoholic Metabolites of Catecholamines in Rat Brain

Abstract: We have investigated the effects of 3, 4-dihydroxyphenylalanine (L-DOPA) and its deuterated analogue on the concentrations of alcoholic metabolites of catecholamines in rat brain by means of gas chromatography/mass spectrometry with selected-ion monitoring. Whole brain concentrations of the two neutral norepinephrine metabolites, 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) and 3, 4-dihydroxyphenylethyleneglycol (DHPG), were significantly increased in a dose-dependent manner by a single intraperitoneal injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…As reported earlier L-dopa treatment alone considerably raised DA levels in the hypothalamus and brain stem but did not change NE concentrations. This finding differs from that of Chalmers et al (1971), who used a fluorometric method to determine NE, but agree with most recent reports (Freed and Murphy, 1978;Edwards and Rizk, 1981;Commissiong, 1984), which used the highly specific GC-MS method to measure NE. NE failed to increase even when DA was injected intraventricularly to give concentrations …”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…As reported earlier L-dopa treatment alone considerably raised DA levels in the hypothalamus and brain stem but did not change NE concentrations. This finding differs from that of Chalmers et al (1971), who used a fluorometric method to determine NE, but agree with most recent reports (Freed and Murphy, 1978;Edwards and Rizk, 1981;Commissiong, 1984), which used the highly specific GC-MS method to measure NE. NE failed to increase even when DA was injected intraventricularly to give concentrations …”
Section: Discussioncontrasting
confidence: 74%
“…On the other hand, as Table 1 indicates, L-dopa treatment led to a moderate increase in MHPG, and this increase was dose-dependent. Edwards and Rizk (1981) reported a similar dose-dependent response of whole brain MHPG to L-dopa administration. Our MHPG values in the hypothalamus and brain stem measured by the present HPLC method are similar to the values obtained by these authors, by GC-MS, which suggests that the HPLC method (Westerink, 1984) is specific.…”
Section: Resultsmentioning
confidence: 55%
“…The earliest time studied was 1 h, so it is possible, but unlikely, that a transient increase in NE did occur before 1 h. However, there is an increase in NE synthesis, which is reflected in a sharp increase in MHPG at 1 h in all regions (Fig. 3) (see also Edwards et al, 1981;Edwards and Rizk, 1981).…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that HT can cross the blood‐brain barrier to appear in the brain, although it must be taken into account that HT may be generated endogenously from dihydroxyphenylacetic acid through dihydroxyphenylacetic reductase of the brain 39 . It can also be generated from dopamine 40 . De la Torre 29 has suggested that our understanding of the function of HT is hampered by the fact that HT is a metabolite of dopamine and that the HT concentration in body fluids is a combination of the exogenous and endogenous sources.…”
Section: Hydroxytyrosolmentioning
confidence: 99%
“…39 It can also be generated from dopamine. 40 De la Torre 29 has suggested that our understanding of the function of HT is hampered by the fact that HT is a metabolite of dopamine and that the HT concentration in body fluids is a combination of the exogenous and endogenous sources. This is the main reason it is not possible to mini-mize its concentration in biological fluids, hindering the evaluation of its availability in the organism, whether after a period without food intake or after strict dietary control.…”
Section: Pharmacokineticsmentioning
confidence: 99%